Family-centred music therapy with preterm infants and their parents in the Neonatal Intensive Care Unit (NICU) in Colombia – A mixed-methods study. Issue 3 (27th May 2017) - Ettenberger, Mark; Rojas Cárdenas, Catherine; Parker, Mike; Odell-Miller, Helen
ABSTRACT: This article reports a mixed-methods study of Music Therapy (MT) with preterm infants and their parents in a neonatal intensive care unit (NICU) in Colombia. The aim was to find out whether live MT during kangaroo care had an effect on the physiological outcomes of the neonates and would help parents to decrease their anxiety levels and improve parent–infant bonding. The participants were 36 medically stable neonates born between the 28th and 34th week of gestation and their parents. The quantitative data collection included heart rate, oxygen saturation, weight gain, length of hospitalization and re-hospitalization rate. The assessment measures for anxiety and bonding were the State-Trait Anxiety Inventory (STAI) and the Mother-to-Infant-Bonding Scale (MIBS). Thematic analysis was used to analyse the qualitative data collected with semi-structured interviews and questionnaires. The quantitative results showed statistically significant improvements in maternal state-anxiety ( p = .007) and in the babies weight gain per day during the intervention period ( p = .036). Positive trends were found regarding the babies' length of hospitalization and re-hospitalization rate. Both parents improved their scores with the MIBS, but this was not statistically significant. The qualitative analysis showed that MT was important for parental well-being, for bonding and for fostering the development of the neonates. Interacting musically with their babies helped parents to experience feelings of connectedness and to distract themselves from their difficulties and from the noisy hospital environment.